Do lipids contribute to the lack of cardio-protective effect of binge drinking: alcohol consumption and lipids in three eastern European countries - Peasey, Anne; Bobak, Martin; Malyutina, Sofia; Pajak, Andrzej; Kubinova, Ruzena; Pikhart, Hynek; Kurilovitch, Svetlana; Poledne, Rudolf; Marmot, Michael (Alcohol and alcoholism (Oxford, Oxfordshire), 2005)
AIMS: The cardio-protective effect of moderate alcohol consumption is partly mediated by HDL cholesterol. However, epidemiological studies suggest that binge drinking may not be associated with reduced risk of heart disease; a possible explanation is that the relationship of blood lipids with binge drinking is different from that with moderate intake. We investigated this hypothesis in a population study in three eastern European countries. METHODS: We conducted a cross-sectional study in random population samples in Novosibirsk (Russia), Krakow (Poland) and Karvina (Czech Republic). A sub-sample of 282 men aged 45-64 years who provided a fasting blood sample were analysed. Annual alcohol intake and the frequency of heavy binge drinking (> or =140 g of ethanol per session) were estimated from a graduated frequency questionnaire. RESULTS: Annual intake of alcohol was positively associated with total and HDL cholesterol. After controlling for annual intake, the frequency of heavy binge drinking was associated with increased concentrations of total and HDL cholesterol. By combining annual intake and drinking pattern, we found that men consuming >8 l of alcohol per year who had a heavy binge at least once a month had the mean total, HDL and LDL cholesterol 1.69 (SE 0.35), 0.61 (0.11) and 0.97 (0.34) mmol/l, respectively, higher than non-drinkers; this resulted in more favourable ratios of total and LDL cholesterol relative to HDL cholesterol in frequent heavy bingers. Triglycerides were not related to alcohol intake or binge drinking. CONCLUSIONS: Blood lipids do not seem to explain the apparent lack of the cardio-protective effect of binge drinking reported in epidemiological studies.
Keywords: Cholesterol, LDL; Poland; Dose-Response Relationship, Drug; Russia; Cross-Sectional Studies; vztah mezi dávkou a účinkem léčiva; lipidy; ethanol; srovnání kultur; Cross-Cultural Comparison; koronární nemoc; Alcoholic Intoxication; Česká republika; Rusko; Middle Aged; Ethanol; mužské pohlaví; otrava alkoholem; průřezové studie; Czech Republic; Polsko; Lipids; Humans; kardiotonika; Cardiotonic Agents; lidé středního věku; rizikové faktory; HDL-cholesterol; LDL-cholesterol; Coronary Disease; Risk Factors; Cholesterol, HDL; lidé; Male